2018
DOI: 10.1111/risa.13206
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cumulative Risk Perception from Judgments and Choices: An Application to Flood Risks

Abstract: Catastrophic events, such as floods, earthquakes, hurricanes, and tsunamis, are rare, yet the cumulative risk of each event occurring at least once over an extended time period can be substantial. In this work, we assess the perception of cumulative flood risks, how those perceptions affect the choice of insurance, and whether perceptions and choices are influenced by cumulative risk information. We find that participants' cumulative risk judgments are well represented by a bimodal distribution, with a group t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 103 publications
(164 reference statements)
0
19
0
Order By: Relevance
“…The results also have implications for some of the challenges demonstrated in conveying cumulative risk in various domains like breast-cancer medication risk (Zikmund-Fisher et al, 2008), contraception methods related risk (De La Maza et al, 2019), stroke risk (Fuller et al, 2004), flood risk (De La Maza et al, 2019), etc. mentioned before.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The results also have implications for some of the challenges demonstrated in conveying cumulative risk in various domains like breast-cancer medication risk (Zikmund-Fisher et al, 2008), contraception methods related risk (De La Maza et al, 2019), stroke risk (Fuller et al, 2004), flood risk (De La Maza et al, 2019), etc. mentioned before.…”
Section: Discussionmentioning
confidence: 93%
“…Extremely small risk levels in the near term can accumulate to become extremely hazardous in the long run when continuous exposure to the same risk factors occurs for a long duration (e.g., smoking for years) or simultaneous exposure to multiple factors (e.g., smoking and drinking). Perceptions of cumulative risk are studied widely in various socially significant issues like smoking (Weinstein, 1998;Slovic, 2000), climate change (Crawford-Brown and Crawford-Brown, 2012), contraceptive failures (Doyle, 1997), floods (De La Maza et al, 2019), Sexually Transmitted Diseases (Knauper et al, 2005), stroke risk (Fuller et al, 2004), medical treatments (Dijkstra et al, 2000), and so on. Most of these risky catastrophic events have a very low probability of happening in a particular month or a year; however, those probabilities can aggregate to a very high cumulative risk over a decade or lifetime, causing significant losses (Slovic et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalizing the common probability-weighting pattern from research on the descriptionexperience gap to this epistemic state, one may expect this physician to behave as if they underweight rare (and possibly delayed; De La Maza, Davis, Gonzalez, & Azevedo, 2019) risks. Their experience tells them that rare events are indeed rare.…”
Section: As-if Underweighting Of Rare Eventsmentioning
confidence: 99%
“…We aim to translate the results of the CDSLR-driven biogeophysical models using FEMA's HAZUS tool to assess increasing ood risk to residential structures and people to a metric that is easily communicated to stakeholders and policy makers. It has been found that the public perception of risk, as communicated in probabilistic-based information, may not always be accurate and can affect their choice in choosing whether to buy ood insurance, for example 34 . Additional research suggests people are more likely to be motivated to hold insurance if they anticipate substantial damages to occur to their homes or businesses, or if they have previous experience with oods 35 .…”
Section: Introductionmentioning
confidence: 99%